(3TQM efXheI GdMGaX Hf aQM GdETHjdjs - (3jMji GdbQGaj Hf YHO GdQMef GdCUagGfjs; (3GHf aQM , CMeO Hf aQM Hf CMeO Hf eMeO Hf aQM GddNej GdGTHjdj, TgGH GdOjf CHh GdYHGS,J (B966 (3g` s
(3ChdgG (B:s
(3hHYO agPG TQM dWja GdMLe MhGaj Yde GdMOjK ef GdahGFO GdLe YedJg Ydi efXheI GdMGaX Hf aQL GdETHjdj s
(3BNQgG (B:s
(3aJchf Jdc GdfGQ HQOkG HdPI GdeMHI hGdhUd bGd Pdc GdabjQ GdeYJQa HGdYLR hGdJbUjQ jMji Hf YHOGdQMef GdCUagGfi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B45s
Keywords: (3GdCOHs